2011
DOI: 10.1016/j.bone.2011.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Suberoylanilide hydroxamic acid (SAHA; vorinostat) causes bone loss by inhibiting immature osteoblasts

Abstract: Histone deacetylase (Hdac) inhibitors are used clinically to treat cancer and epilepsy. Although Hdac inhibition accelerates osteoblast maturation and suppresses osteoclast maturation in vitro, the effects of Hdac inhibitors on the skeleton are not understood. The purpose of this study was to determine how the pan-Hdac inhibitor, suberoylanilide hydroxamic acid (SAHA; a.k.a. vorinostat or Zolinza™) affects bone mass and remodeling in vivo. Male C57BL/6 mice received daily SAHA (100 mg/kg) or vehicle injections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 70 publications
2
79
2
Order By: Relevance
“…Expression levels of mRNAs for Runx2, Axin2, and Gapdh were measured by real-time PCR. Primer sequences were reported previously (32,33). Reactions were performed using 37.5 ng of cDNA/15 l with Bio-Rad iQ SYBR Green Supermix and the Bio-Rad MyiQ single color real-time PCR detection system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression levels of mRNAs for Runx2, Axin2, and Gapdh were measured by real-time PCR. Primer sequences were reported previously (32,33). Reactions were performed using 37.5 ng of cDNA/15 l with Bio-Rad iQ SYBR Green Supermix and the Bio-Rad MyiQ single color real-time PCR detection system.…”
Section: Methodsmentioning
confidence: 99%
“…For gene expression studies, RNA was harvested with TRIzol reagent (Invitrogen) after 7, 14, or 21 days in osteogenic culture. RNA was reverse transcribed and expression levels of Runx2 or Bglap (genes associated with osteoblast maturation) were quantified as described above and previously (32).…”
Section: Methodsmentioning
confidence: 99%
“…Using an in vivo model, it was demonstrated that vorinostat resulted in bone loss and reduced osteoblast numbers in mice [77]. Despite a negative effect on the immature osteoblasts, an increase in local bone formation was observed, with mature osteoblasts possibly being resistant to HDACi-induced apoptosis [77]. Selective targeting and lower doses (10-100x lower) of HDACi have been shown to be better tolerated in animal models and have different effects on bone cells without the induction of apoptosis.…”
Section: General Effects Of Hdaci On Bone Formationmentioning
confidence: 99%
“…HDACi are known to directly target cancer cells by increasing expression of many proteins including those that regulate tumor suppression, DNA repair, and cell-cycle arrest. Because HDACi have also been shown to alter expression of many genes within cells of the osteoblast lineage (15)(16)(17)(18), we hypothesized that HDACi might also target the leukemic microenvironment. HDACi have been previously shown to up-regulate Nherf1 (also known as EBP-50), a scaffold protein mutated in human hypophosphatemic nephrolithiasis/osteoporosis type 2.…”
mentioning
confidence: 99%